Synthesis, in vitro cytotoxic and apoptotic effects, and molecular docking study of novel adamantane derivatives - (:unkn) unknown (WILEY-V C H VERLAG GMBH, 2021)
[4-(Adamantane-1-carboxamido)-3-oxo-1-thia-4-azaspiro[4.4]nonan-2-yl]acetic acid (4a) and [4-(adamantane-1-carboxamido)-8-nonsubstituted/substituted-3-oxo-1-thia-4-azas-piro[4.5]decane-2-yl]acetic acid (4b-g) derivatives were synthesized; their structures were verified by elemental analysis, infrared spectroscopy, H-1 nuclear magnetic resonance (NMR), C-13 NMR, and mass spectroscopy data; and their in vitro cytotoxicity activities were investigated against human hepatocellular carcinoma, human prostate adenocarcinoma, and human lung carcinoma cell lines (HepG2, PC-3, and A549, respectively), and a mouse fibroblast cell line (NIH/3T3). All compounds, except compound 4e, were found as cytotoxic, especially on A549 cells as compared with the other cells (selectivity index = 2.01-11.6). As a further step, the effects of compounds 4a-c on apoptosis induction were tested and the expression of selected apoptosis genes was analyzed. Among the selected compounds, compound 4a induced apoptosis remarkably. Moreover, computational calculations of the binding of compounds 4a-c to the BIR3 domain of the human inhibitor of apoptosis protein revealed ligand-protein interactions at the atomistic level and emphasized the importance of a hydrophobic moiety on the ligands for better binding.
Keywords: antitumor activity; cytotoxic activity; structure elucidation; synthesis; thiazolidine; ANTIINFLUENZA VIRUS ACTIVITY; LUNG-CANCER CELLS; ANTIPROLIFERATIVE ACTIVITY; ANTIMICROBIAL ACTIVITY; BIOLOGICAL EVALUATION; ANTIBACTERIAL; EXPRESSION; INHIBITORS; HALLMARKS; PROTEINS